2017
DOI: 10.1038/srep42411
|View full text |Cite
|
Sign up to set email alerts
|

TRIM14 regulates cell proliferation and invasion in osteosarcoma via promotion of the AKT signaling pathway

Abstract: Recent studies have shown that some members of the tripartite motif-containing protein (TRIM) family serve as important regulators of tumorigenesis. However, the biological role of TRIM14 in osteosarcoma remains to be established. In this study, we showed that TRIM14 is upregulated in human osteosarcoma specimens and cell lines, and correlated with osteosarcoma progression and shorter patient survival times. Functional studies demonstrated that overexpression of TRIM14 enhances osteosarcoma cell proliferation,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
54
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 60 publications
(58 citation statements)
references
References 29 publications
1
54
0
Order By: Relevance
“…Wang et al had reported that TRIM14 overexpression induced EMT and resulted in the formation of cancer‐initiating cells and acquisition of a chemoresistant phenotype by oral tongue squamous cell cancer. TRIM14 was further reported to enhance migration and invasion of osteosarcoma cells and gastric cancer cells by regulating EMT transition via activation of the Akt signaling pathway, which may correspond to the attainment of CSC‐like phenotype. Similar to TRIM27, the exact molecular mode of TRIM14 action in Akt signaling promotion requires further investigation, because neither TRIM14 nor TRIM27 can phosphorylate Akt and other downstream targets.…”
Section: The Engagement Of Specific Trims In Stem Cell Maintenancementioning
confidence: 99%
See 1 more Smart Citation
“…Wang et al had reported that TRIM14 overexpression induced EMT and resulted in the formation of cancer‐initiating cells and acquisition of a chemoresistant phenotype by oral tongue squamous cell cancer. TRIM14 was further reported to enhance migration and invasion of osteosarcoma cells and gastric cancer cells by regulating EMT transition via activation of the Akt signaling pathway, which may correspond to the attainment of CSC‐like phenotype. Similar to TRIM27, the exact molecular mode of TRIM14 action in Akt signaling promotion requires further investigation, because neither TRIM14 nor TRIM27 can phosphorylate Akt and other downstream targets.…”
Section: The Engagement Of Specific Trims In Stem Cell Maintenancementioning
confidence: 99%
“…However, for several TRIMs, the molecular mode of action is yet not fully understood and the data suggest the participation of additional factors. 36,38,39,48 Similarly, TRIM-mediated regulation of core pluripotency transcription factor machinery is based on the E3 ubiquitin ligase activity (mediated by the RING domain) 32,55,60 or the ability to form a complex and stabilize specific transcription factors 14,50,51 (unfortunately, it has not been precisely defined whether the TRIM motif is always required for protein-protein interactions).…”
Section: Other Trim Family Members Potentially Involved In the Regumentioning
confidence: 99%
“…TRIM14 promotes breast cancer cell proliferation by inhibiting apoptosis [15]. TRIM14 regulates cell proliferation and invasion in osteosarcoma via promotion of the AKT signaling pathway [16].However, the expression levels and biological functions of TRIM14 in glioblastoma remain to be elucidated.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, the process known as “cadherin switching” (downregulation of E-cadherin and upregulation of mesenchymal cadherins such as N-cadherin [28]) and the accumulation of β-catenin have also been associated with EMT [29]. Previous studies have revealed the increased EMT characteristics in OS cells and demonstrated the involvement of EMT in OS invasiveness and migration [3033]. In our study, the decreased invasive ability of the U2OS cell line induced by the depletion of SOX3 prompted us to investigate whether SOX3 is involved in EMT.…”
Section: Discussionmentioning
confidence: 99%